Plant growth-promoting rhizobacteria induce changes in Arabidopsis thaliana gene expression of nitrate and ammonium uptake genes. Issue 1 (1st January 2019) - Calvo, Pamela; Zebelo, Simon; McNear, David; Kloepper, Joseph; Fadamiro, Henry
ABSTRACT: Plant growth-promoting rhizobacteria (PGPR) enhance plant growth under the influence of multigenic processes, including nitrate ( N O 3 − ) and ammonium ( N H 4 + ) uptake genes, which could potentially explain the improvement in plant nutrition and plant growth promotion. Studies on the effects of PGPR inoculation on regulation of N O 3 − and N H 4 + plant uptake genes and nutrient accumulation using soil or soil-like substrates are limited. Here, we tested the hypothesis that the application of PGPR Bacillus mixtures increases overall plant growth, nutrient uptake and the transcript levels of nitrate and ammonium uptake genes in Arabidopsis thaliana . All three PGPR mixtures tested in this study significantly increased plant shoot fresh weight, root fresh, chlorophyll content, nutrient uptake and plant diameter. The transcript levels of five nitrate and four ammonium uptake genes were significantly higher in PGPR-treated plants compared to untreated plants. These results demonstrate that plant growth promotion and enhanced nutrient uptake by select PGPR mixtures.